Anticancer effects of gingerol, shogaol and curcumin in cervical cancer: a systematic review protocol - Che Roos, Nur Aishah; Rahim, Unwaniah Abdull; Mustapa, Marami; Nurdin, Armania; Taridi, Nursiati Mohamad; Mohd Yusof, Yasmin Anum (Medknow Publications, 2023)
Background: Cervical cancer has accounted for the top-four cancer incidences occurring among females worldwide. Despite the availability of anticancer drugs as one of its treatment modalities, they are not without adverse effects. It has come to researchers’ attention that natural bioactive compounds have anticancer properties, as reported in many pre-clinical studies. Materials and Methods: This systematic review protocol conforms to the Preferred Reporting Items for Systematic Review and Meta-analysis Protocols-P guideline and Population, Intervention, Comparison Outcome and Study framework. Electronic databases, including PubMed, Scopus and ScienceDirect, will be searched from inception until May 2022 for articles published in English. Only studies that investigate the effects of curcumin, gingerol, shogaol and/or their combination in human cervical cancer cell lines and/or rodent animal models implanted with cervical cancer xenografts will be included. A customised risk-of-bias tool (RoB) and the Systematic Review Centre for Laboratory Animal Experimentation’s RoB will be used to assess the quality of in vitro and in vivo studies, respectively. Where appropriate, a meta-analysis will be performed using RevMan version 5.4. Conclusions: Findings obtained from this review may be used as valuable evidence to guide and direct future studies pertaining chemopreventive effects of bioactive compounds in cervical cancer. This protocol is registered on PROSPERO (CRD42022334940).